Usuń nawiasy i wykonaj redukcję wyrazów podobnych :
a) (a+b)+(2a-b)=
b) 2x+(3y-2z)+(3z-2x)=
c) -5ab+(bc-2ab)+4cb=
d) (5xyz-2xz)+(4zx-7zyx)=
e) (m+n)-(2m+3n)=
f) (2xy+4y²)-(3yx+2y²)=
g) 3abc-(2cab+5bac)=
h) 10x²y-(5xy²-8x²y)=


baardzo mi to potrzebne jest !! pomocyyy !!

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T21:50:59+01:00
A)
(a+b)+(2a-b)=
a+b+2a-b=
3a

b)
2x+(3y-2z)+(3z-2x)=
2x+3y-2z+3z-2x=
3y+z

c)
-5ab+(bc-2ab)+4cb=
-5ab+bc-2ab+4cb=
-7ab+5cb

d)
(5xyz-2xz)+(4zx-7zyx)=
5xyz-2xz+4zx-7zyx=
-2xyz+2xz

e)
(m+n)-(2m+3n)=
m+n-2m-3n=
-m-2n

f)
(2xy+4y"kwadratowe")-(3yx+2y"kwadratowe")=
2xy+4y²-3yx-2y²=
-xy+2y²

g)
3abc-(2cab+5bac)=
3abc-2cab-bac=
0


h)
10x"kwadratowe"y-(5xy"kwadratowe"-8x"kwadratowe"y)=
10x²y-5xy²+8x²y=
18x²y-5xy²
49 4 49
2010-03-21T21:54:46+01:00
A) (a+b)+(2a-b)= a + b + 2a - b = 3a
b) 2x+(3y-2z)+(3z-2x)= 2x + 3y - 2z + 3z - 2x = 3y + z
c) -5ab+(bc-2ab)+4cb= -5ab + bc - 2ab + 4bc = -7ab + 5bc
d) (5xyz-2xz)+(4zx-7zyx)= 5xyz - 2xz + 4xz - 7xyz = -2xyz + 2xz
e) (m+n)-(2m+3n)= m + n - 2m - 3n = -m - 2n
f) (2xy+4y"kwadratowe")-(3yx+2y"kwadratowe")= 2xy + 4y² - 3xy - 2y² = -xy + 2y²
g) 3abc-(2cab+5bac)= 3abc - 2abc - 5abc = -4abc
h) 10x"kwadratowe"y-(5xy"kwadratowe"-8x"kwadratowe"y)= 10x²y - 5xy² + 8x²y = 18x²y - 5xy²
11 3 11
2010-03-21T22:03:28+01:00
A) = a+b+2a-b=3a
b)= 2x+3y-2z+3z-2x=3y+z
c)=-5ab+bc-2ab+4cb=-7ab+bc+4cb=-7ab+5bc
d)=5xyz-2xz+4zx-7zyx=-2xyz+2xz
e)=m+n-2m-3n=m+2n
f)=2xy+4y(kwadrat)-3yx+2y(kwadrat)=6y(kwadrat)-xy
g)=3abc-2abc-5bac=4abc
h)10x(kwadrat)y-5xy(kwadrat)+8x(kwadrat)y=18x(kwadrat)y-5xy(kwadrat)



8 3 8